Attitudes about violence against women in intimate relationships - new measuring instruments and the results from two Croatian Universities - Klasnić, Ksenija, sociologinja (2012)
Violence always presumes the abuse of power in relationships based on inequality (Ajduković, Pavleković, 2000). Violence against women in intimate relationships is manifested in various forms. Most often one can talk about mental, physical, sexual and economic violence. But while many people perceive violence against women solely in its physical form, sometimes even certain forms of physical assaults are not characterized as violence. We began our research under the assumption that the perception of violence is such that the term “violence” usually involves only physical violence, although this term is actually much broader and includes all other forms of partners’ violent behavior which are recognized to a lesser extent. Less recognition of other forms of violence indicates social tolerance towards violence which was in this study measured by three main indicators: reduction of offenders’ responsibility, shifting responsibility to the victim and finding external circumstances which can “explain” violent behavior. The presentation will be based on the results of a research conducted on a sample of students from the University of Zagreb and the University of Split, in which we examined male and female stereotypes on violence against women and also their recognition and attitudes about various forms of violence in intimate relationships (physical, sexual, psychological and economic). The aim of the study was to determine which are the most common stereotypes about violence in intimate relationships and whether there are some connections between these stereotypes and recognition of different forms of domestic violence, sexism, and some socio-demographic and socio-cultural characteristics of students such as sex, place of growing up, parents' educational level, social status family, etc. This research also represents a methodological novum in the study of attitudes about violence against women. Specifically, these attitudes were measured using instruments in the form of six short stories in which the main characters were man and woman in intimate relationship, each describing one everyday life situation with one of the four specified forms of violence in intimate relationships. After each story respondents were asked to dichotomously assess the roles of the characters and also to give a general assessment of the context of each story.